Optimizing prickly pear by-product valorization: formulating molasses with enhanced antioxidant capacities and sugar contents. - Yazidi, Raghda; Yeddes, Walid; Djebali, Kais; Hammami, Majdi; Aidi-Wannes, Wissem; Ben Farhat, Mouna; Msaada, Kamel; Saidani Tounsi, Moufida (International Journal of Environmental Health Research, 2024)
This study endeavoured to capitalize on prickly pear by-products for the optimization of molasses formulation, targeting elevated antioxidant capacities and superior sugar contents. Through robust statistical modelling, the optimal cooking parameters—temperature (70-80 °C) and duration (60–90 min)—were determined, guided by responses of antioxidant activity and Brix value. A D-Optimal mixture design further delineated the ideal proportions of molasses components (pulp, peel, and seeds). Characterization revealed that peel harboured the highest concentrations of total polyphenols (396.41 mg GAE/100g FW) and flavonoids (234.26 mg CE/100g FW), emphasizing its antioxidant potential (DPPH inhibition IC50: 12.72 µg/ml). The optimal cooking conditions were established at 78.35 °C for 79.70 min, with predictive equations guiding ingredient proportions (0.265 g pulp, 0.710 g peel, 0.025 g seed). Intriguingly, while peel inclusion enhanced total sugar content and antioxidant activity, seed incorporation exerted a contrasting effect by reducing total sugar content and limiting antioxidant activity.